Social Transformation of the Saribu Rumah Gadang Indigenous Tourism Area: Analysis of Nobert Elias Social Figures - Rahmaini, Indah Sari (Talenta Publisher, 2022)
The reduced interest of the Minangkabau indigenous people in building and maintaining a Rumah Gadang is caused by the rapid acceleration of industrialization, modernization, and market competition. However, South Solok Regency has a Rumah Gadang which is still well maintained with a very good layout. This condition makes the area of high value and attracts tourists from various regions, including foreign tourists in the context of traditional tourism villages. This article aims to describe the regional social transformation that occurs in the traditional tourist area of Saribu Rumah Gadang. This paper uses the social figuration theory of Nobert Elias as his analytical knife. This article uses a qualitative approach with a descriptive method. The results are that there are various transformations of the concept of the Rumah Gadang, the transformation of space as a common space, and social transformation as ethical behavior in the Rumah Gadang. The conclusion of this study is that Rumah Gadang is no longer a residence for extended families, but is a traditional tourist destination. The transformation that occurs both physically and socially is caused by the interdependence, habitus, and figuration that are intertwined with the social relations established by the Minangkabau community with other communities.